Factors affecting the participation of oil palm smallholders in controlling Ganoderma Basal Stem Rot disease - Nur Izzaty Iqlima Norazman (2019)
Oil palm Basal Stem Rot disease or Ganoderma is one of the most serious threats faced not only by the large scale oil palm estates, but also oil palm smallholders who have been playing a very vital role in the Malaysian oil palm industry. Unfortunately, many oil palm smallholders were unaware that their fields were being infected with Ganoderma, and they failed to recognize the extent of the disease incidence. Therefore, this study was conducted to evaluate the knowledge level of oil palm smallholders on detection, curative control and preventive control of Ganoderma disease associated with the socioeconomic background, to evaluate the practices of oil palm smallholders towards the Ganoderma disease associated with the socioeconomic background and to identify the attitude factors affecting the participation of oil palm smallholders in controlling Ganoderma disease Besides that, the relationships between knowledge and practices with their socioeconomic factors were also identified. Cross-sectional survey through purposive multi-stage random sampling using structured questionnaire was the approach used in gathering data from 510 oil palm smallholders consisting of organised and independent smallholders in six states of peninsular Malaysia. Based on the cluster analysis, the oil palm smallholders were categorized as less knowledgeable smallholders and knowledgeable smallholders towards the Ganoderma disease. From the Chi-square comparison test, significant relationships were found between category of smallholders, experience in oil palm cultivation and age of smallholders with level of knowledge on Ganoderma disease. Meanwhile, significant relationships were found between preventive control practices of oil palm smallholders with category of smallholders by using binary regression analysis. The results of factor analysis identified three main aspects of attitude of oil palm smallholders towards Ganoderma disease. It could be concluded that the knowledge of oil palm smallholders towards Ganoderma disease was still limited. This could be seen from their perceptions about the lack of exposure and having constraints in managing the disease. As a result, they took only little action on the treatment and prevention of the disease. The findings of this study, hopefully, could be used by relevant agencies as a source of reference in the formulation of comprehensive training programs, and also to really convince the oil palm smallholders especially in the Peninsular Malaysia about the socioeconomic impacts of the Ganoderma disease.